Upaya Pencegahan Demam Berdarah Dengue Melalui Edukasi Kesehatan di Desa Jua Jua - Eka Afrika; Rizki Amalia; Putu Lusita Nati Indriani; Erma Puspita Sari; Annisa Syahrani; Caria Sonesti; Cerli Maulidina; Della Ayuni; Dellah Fuspita Yusantika; Delon Novaringga; Eka Safitri Dayanti; Fega Fega; Ferdy Ahmad Yani; Melinda Melinda; Putri Femiliyah; R.A Adibah Afrahnisa; Reno Lorenza (JURNAL PENGABDIAN KADER BANGSA, 2026)
Dengue Hemorrhagic Fever (DHF) is an infection caused by the dengue virus and transmitted through the bite of the Aedes aegypti mosquito. This disease remains a relevant public health issue in Indonesia, necessitating preventive measures through public education. This community service program aims to increase public knowledge and awareness regarding the risks of DHF and prevention methods. The chosen approach is direct outreach and outreach to residents of Jua Jua Village, Kayu Agung District. This activity involves providing information on the causes, modes of transmission, signs, and preventive measures for DHF, such as maintaining environmental cleanliness, combating mosquito breeding sites, and using mosquito repellents. The results of this activity indicate that the community is becoming more aware of the importance of maintaining environmental cleanliness to prevent the increase in the mosquito population that causes DHF. The enthusiasm shown by the community during this program indicates an increased awareness of disease prevention efforts. Therefore, this outreach is expected to provide support to the community in preventing DHF cases in the Jua Jua Village area.